The role of research work of students in the educational process of a university - L. V. Rozhkova; A. Sh. Dubina; E. B. Teplyakov (Вестник Майкопского государственного технологического университета, 2025)
Introduction. Today social transformations affect all aspects of society. Rapid changes in society, economy, culture, politics and other areas lead to changes in value orientations. Technological progress and the active use of artificial intelligence inevitably lead to a revision of the traditional requirements for the profession, which in turn creates modern trends in the system of student training in higher education institutions. Thus, the introduction of new technologies and transformations in society replace the usual competencies, expecting employees to have skills that correspond to the trends of the modern world, thereby creating prospects for the development of society.The Materials and Methods. The article uses the results of sociological research by Russian scientists, and the authors conducted a focus group discussion among students of Penza State University and in-depth interviews with potential employers of the Penza region.The Results. The article presents the reasons for the need to introduce research work into the educational process of students at the university. Special attention is paid to the study of the correspondence of employers' needs to the competencies of applicants and the expectations of graduates about the requirements for successful employment. Sociological research has shown that the views of modern Russian youth on the need to introduce scientific and creative work differ from those of employers. Since not all students support the decision to include additional classes related to scientific research and creative work in their studies, since they do not see its benefits for themselves at the present time and in the future. At the same time, employers express the need for graduates with scientific and creative skills.Discussion and Conclusion. It has been concluded that a positive effect should be expected from attracting students to research, but on condition that they are constantly included throughout the entire period of study. In higher education it is necessary to create favorable conditions for the scientific activity of students: to organize the work of scientific interest groups, to provide the necessary material and technical equipment, to provide scientific and methodological material and to stimulate work by encouraging morally and financially.